Relative abundance and resource characteristics of penaeid prawn seed in Orissa coast - Mohanty, Rajeev K; Patnaik, P N (Indian Journal of Fisheries, 2011)
To study the relative abundance and resource characteristics of penaeid prawnseed (Penaeus monodon and P. indicus) along the Orissa coastal belt, ten seedcollection centres in six estuarine areas were selected. Two peaks of abundancewere noticed for P. mondon (April-June and November-December) and P. indicus(April-June and October-December), although their post larvae were availablethroughout the year. From the annual average CPUE (catch per unit effort)data of ten collection centres and chances of frequency for economic operation ofnets, the total number of P. monodon and P. indicus, juveniles that may beavailable for collection annually, have been estimated for each centre, whichranged between 0.105-10.557 million and 0.06-22.95 million respectively. TheCPUE during high tide phase was significantly higher (p<0.05) than that of lowtide phase. Correlation of water salinity with post larval abundance was highlysignificant (p<0.001) and the most preferred salinity range was 27.30-32.25 ppt.